Case Report: Hydroxychloroquine in an infant with NKX2-1-associated interstitial lung disease - Qing, Di; Xu, Xuehua; Shi, Tingting; Fan, Huifeng; Zhang, Dongwei; Yang, Diyuan; Lu, Gen (Frontiers in Pediatrics, 2025)
This study presents a case of brain–lung–thyroid syndrome caused by a pathogenic variant in the NKX2-1 gene, which is characterized by interstitial lung disease. A 7-month-old female infant was hospitalized for over half a month for cyanosis. The full-term infant developed respiratory distress syndrome soon after delivery, requiring mechanical ventilation, and was diagnosed with congenital hypothyroidism. In the first seven months of life, the infant also showed hypotonia, feeding difficulties, and developmental delays. Chest CT findings demonstrated generalized ground-glass opacities in both lung fields. A heterozygous pathogenic variant of the NKX2-1 gene [NM_001079668.3:c.583C>T (p.Arg195Trp)] was identified by whole-exome sequencing. The infant received a combination therapy, comprising supplementary thyroxine, nutritional support, high-flow nasal cannula oxygen therapy, and exploratory treatment with hydroxychloroquine. High-flow nasal cannula oxygen therapy was administered after discharge. The patient was followed up for over 2 months, and the patient had changed to low-flow oxygen therapy, although she developed radiographic progression. Studies on hydroxychloroquine for the treatment of interstitial lung diseases are limited. This article describes a case of interstitial lung disease caused by a pathogenic variant in the NKX2-1 gene, whose oxygen demand decreased after treatment with hydroxychloroquine.